Effect of silicon and phosphorus fertilization on growth, productivity and profitability of aerobic rice (Oryza sativa) - JINGER, DINESH; DHAR, SHIVA; DASS, ANCHAL; SHARMA, V K; JOSHI, EKTA; VIJAYAKUMAR, S; GUPTA, GAURENDRA (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted at ICAR- Indian Agricultural Research Institute, New Delhi during rainy (kharif) seasons of 2015 and 2016 to study the effect of silicon and phosphorus levels on yield, yield attributes and economics of aerobic rice (Oryza sativa L.). Four levels each of phosphorus (0, 30, 60 and 90 kg P2O5/ha) and silicon (0, 40, 80 and 120 kg Si/ha) were tested in a factorial randomized block design (FRBD) and replicated three times. Growth and yield attributes were significantly higher when phosphorus and silicon were included in the nutrient management of aerobic rice cultivation. Growth, yield, yield attributes and economics were significantly affected by the combined application of silicon and phosphorus. The highest aerobic rice grain yield (5.66 and 5.62 t/ha), net returns (Rupees 92.4×103 /ha and 90.1×103 /ha) and yield attributes were recorded with 90 kg P2O5 /ha during both the years of experimentation. However, it was at par with 60 kg P2O5 /ha during both the years of experimentation. In case of silicon application, highest grain yield (5.53 and 5.65 t/ha), net returns (Rupees 90.7×103 /ha and 92.4×103 /ha) and yield attributes were recorded with 120 kg Si/ha, however, it was at par with 80 kg Si/ha during both the years of experimentation. Therefore, the application of phosphorus and silicon should be adopted for achieving higher productivity and profitability of aerobic rice.